Implementasi Internet of Things (IoT) dalam Monitoring Kualitas Air untuk Pertanian Berkelanjutan - Jeana Anastasya (Jurnal Sains dan Teknologi Indonesia, 2025)
This study explores the implementation of Internet of Things (IoT) technology in monitoring water quality to support sustainable agriculture. The increasing demand for food requires efficient resource management, particularly in water use. IoT-based monitoring systems provide real-time data on water quality parameters such as pH, dissolved oxygen, temperature, and turbidity, enabling farmers to make data-driven decisions. Through literature review and analysis of previous studies, this research identifies the potential of IoT in optimizing water usage, reducing environmental impact, and supporting precision agriculture practices. The findings highlight that IoT integration contributes significantly to sustainable farming by improving water management efficiency, enhancing crop productivity, and minimizing resource wastage.